Hydration of nitriles using a metal-ligand cooperative ruthenium pincer catalyst - Guo, Beibei; de Vries, Johannes G; Otten, Edwin (Chemical science (Cambridge), 2019)
Nitrile hydration provides access to amides that are important structural elements in organic chemistry. Here we report catalytic nitrile hydration using ruthenium catalysts based on a pincer scaffold with a dearomatized pyridine backbone. These complexes catalyze the nucleophilic addition of H 2 O to a wide variety of aliphatic and (hetero)aromatic nitriles in t BuOH as solvent. Reactions occur under mild conditions (room temperature) in the absence of additives. A mechanism for nitrile hydration is proposed that is initiated by metal-ligand cooperative binding of the nitrile. The hydration of a broad range of aliphatic and (hetero)aromatic nitriles is reported via catalysis by metal-ligand cooperative Ru pincer complexes under very mild conditions.